Bioavailability of Polyphenol Liposomes: A Challenge Ahead - Guy G. Chabot; Nathalie Mignet; Johanne Seguin (Pharmaceutics, 2013)
Dietary polyphenols, including flavonoids, have long been recognized as a source of important molecules involved in the prevention of several diseases, including cancer. However, because of their poor bioavailability, polyphenols remain difficult to be employed clinically. Over the past few years, a renewed interest has been devoted to the use of liposomes as carriers aimed at increasing the bioavailability and, hence, the therapeutic benefits of polyphenols. In this paper, we review the causes of the poor bioavailability of polyphenols and concentrate on their liposomal formulations, which offer a means of improving their pharmacokinetics and pharmacodynamics. The problems linked to their development and their potential therapeutic advantages are reviewed. Future directions for liposomal polyphenol development are suggested.